Assessment of Altered Sensation and Functional Effects in Post-Operative Bilateral Mandibular Sagittal Split Osteotomy Patients: a Follow-up Study - Kinza Ayub; Kamran Khan (Pakistan Journal of Medical Research, 2020)
Background: Bilateral sagittal split osteotomy aims to improve and correct functional problems related with facial defects and aesthetics. But osteotomies are placed in closed vicinity with the inferior alveolar nerve hence an incidence of nerve paresthesia producing sensory and functional effects has been reported. Objective: The purpose of this study was to report the incidence of nerve paresthesia (and problems they face due to altered sensation and function) immediately, on six months and one year follow up in patients undergoing the procedure of bilateral sagittal split osteotomy. Study settings & duration: The study was conducted at Islamic International Dental College & Hospital, Islamabad over a period of five years starting from 2013 to 2017. Methodology: The sample population consisted of 18 operated subjects who had undergone bilateral sagittal split osteotomies between the years 2013 and 2017 at the Department of Maxillofacial Surgery at Islamic International Dental Hospital Islamabad. Patients were called to hospital at three different intervals i-e 0 months, six months and 1 year after the surgery. They were asked to answer several questions regarding their perceived sensory changes after the operation by selecting a word from a standardized list describing altered sensation. Results: Seventeen patients had changes in sensation immediately after the surgery. And all the seventeen patients had changes in sensation in lower lip and chin. Seven patients have hypoesthetic sensation, one patient had paresthetic and two patients had dysesthesic sensation one year after the surgery. no patient had pain due to altered sensation immediately, six months or one year after the surgery. Conclusion: More than half of the operated subjects have some sort of paresthesia one year after the surgery. But only two patients had functional problem and one patient had speaking problem due to altered sensation.